ANALISIS PENGARUH SEKTOR PARIWISATA DAN PDRB (non migas-non pertanian) TERHADAP PENINGKATAN PAD DI KABUPATEN LOMBOK UTARA - Fariantin, Erviva; Amri, Syaiful (Valid Jurnal Ilmiah, 2017)
Local Own-source Revenue is the revenue earned from the area collected by local regulations in accordance with the legislation. Source of revenue under the Act include Local Own-source Revenue, Fiscal Balance Transfers, Regional Loan and others. Tanjung is the capital of North Lombok (KLU), Government of North Lombok finally has full authority to manage its own country so the consequence is an increase demand in the region's autonomy. The development of tourism can be used as land that could boost economic improvement. Number of tourists visiting North Lombok from 2010 until 2014 always increase, the number of 1,983,113 people with average visits reached 396 623 people, and the highest number of visits made by foreign tourists every year. The purpose of this study was to determine whether there is influence simultaneously and partially the number of attractions, the number of tourists and the Gross Domestic Regional Product (non oil and non agricultural) to increase Local Own-source Revenue in North Lombok regency. This study focused on North Lombok regency of West Nusa Tenggara tourism sector in view of the many attractions of the area is very interesting and has the potential to be developed to study literature as data collection techniques. The type of data in this research is quantitative and qualitative data, while the source of its data from the Office of Tourism, Local Revenue Offices, and the Office of the Central Bureau of Statistics North Lombok regency. The data analysis used is multiple linear regression analysis to test the classical assumption, or the simultaneous F test and t test or partial. Based on the findings, data analysis and the above discussion it can be concluded that the number of attractions, the number of tourists and the Gross Domestic Regional Product (non oil and non agricultural) simultaneously affect the Local Revenue North Lombok with a value of F table (23.668 > 0216) with a significant level below 0.05 is 0.000. As for the number of attractions, the number of tourists and Gross Domestic Regional Product (non oil and non agricultural) partially no effect on the original income North Lombok with a value (t) table (0428 < 12 706).